Design and development of a service-oriented wrapper system for sharing and reusing distributed geoanalysis models on the web. (January 2019) - Zhang, Fengyuan; Chen, Min; Ames, Daniel P.; Shen, Chaoran; Yue, Songshan; Wen, Yongning; Lü, Guonian
Abstract: Geoanalysis models are an abstraction and expression of geographic phenomena and processes which are associated to environmental issues. Such models continue to be created in many different domains, and collaborative modeling and simulation using models in the open web environment is becoming popular for geographic and environmental research. Service-oriented sharing and reusing of distributed geoanalysis models is an important foundation of this type of work. However, service-oriented modeling faces several challenges, especially associated with reusing heterogeneous geo-simulation model resources. This paper builds on research related to creating, managing, and publishing plug-and-play model services, with the aim to design and develop a web-based wrapper system for geoanalysis models that acts as a service loader and manager to publish these models as services to users. Our wrapper system can accomplish functions such as standardizing model preparation workflows, managing model services, and invoking interactive model services, thus bridging the gap between geo-simulation resource contributors and service users. We use the Soil and Water Assessment Tool (SWAT) model and the Unstructured Grid Finite Volume Community Ocean Model (FVCOM) as case studies to show that the developed wrapper system can readily and efficiently enable sharing of model resources and can contribute to collaborative modeling and simulation for environment across a network. Highlights: Reusing geo-analysis models as services in the web environment. Standardizing heterogeneous models by encapsulation. Managing strategies for kinds of simulation resources. Providing service users with interfaces for running model services.